Lost in the Net? Broadband Internet and Youth Mental Health - Dante Donati; Ruben Durante; Francesco Sobbrio; Dijana Zejcirovic (Center for Economic Studies and ifo Institute (CESifo), 2022)
How does the internet affect young people's mental health? We study this question in the context of Italy using administrative data on the universe of cases of mental disorders diagnosed in Italian hospitals between 2001 and 2013, which we combine with information on the availability of high-speed internet at the municipal level. Our identification strategy exploits differences in the proximity of municipalities to the pre-existing voice telecommunication infrastructure, which was previously irrelevant but became salient after the advent of the internet. We find that access to high-speed internet has a significant positive effect on the incidence of mental disorders for young cohorts but not for older ones. In particular, internet access leads to an increase in diagnoses of depression, anxiety, drug abuse, and personality disorders - for both males and females - and of eating and sleep disorders - for females only. We find similar results for urgent and compulsory hospitalizations and self-harm episodes. These results suggest that the effect of broadband is driven by a rise in the underlying prevalence of mental disorders and not merely by increased awareness about these pathologies.
Keywords: I12; I31; L82; L86; 330; mental health; internet; ADSL; 3G